Prototype Sistem Pendeteksi dan Penetralisir Asap Rokok pada Ruangan dengan Fitur Monitoring Suhu dan Kelembaban - Firra Azzarah Trie Utami; Werman Kasoep; Nefy Puteri Novani (Universitas Andalas, 2022)
This research was conducted with the aim of detecting and neutralizing cigarette smoke in a room using a messaging application—in this term is Telegram as notification to the user. The system is also equipped with room temperature and humidity monitoring features. In a room that is exposed to cigarette smoke does not have good air circulation, it will cause cigarette smoke not to come out quickly, this problem which will interfere with health, because of the smoke that is inhaled. In this case, we need a system that can detect and neutralize cigarette smoke. For cigarette smoke detection using the MQ-7 sensor, the DC fan and Ozone Generator will automatically turn on if the value on the MQ-7 sensor is greater than or equal to 74 Ppm and the system will also send a notification via Telegram that cigarette smoke is detected. This serves to neutralize air contaminated with cigarette smoke in the room. To monitor room temperature and humidity using the DHT11 sensor and the results of room temperature and humidity monitoring will be displayed on the mobile application.